The cost-effectiveness of dual mobility in a spinal deformity population with high risk of dislocation: a computer-based model. (October 2018) - Elbuluk, A. M.; Slover, J.; Anoushiravani, A. A.; Schwarzkopf, R.; Eftekhary, N.; Vigdorchik, J. M.
Abstract : Aims: The routine use of dual-mobility (DM) acetabular components in total hip arthroplasty (THA) may not be cost-effective, but an increasing number of patients undergoing THA have a coexisting spinal disorder, which increases the risk of postoperative instability, and these patients may benefit from DM articulations. This study seeks to examine the cost-effectiveness of DM components as an alternative to standard articulations in these patients. Patients and Methods: A decision analysis model was used to evaluate the cost-effectiveness of using DM components in patients who would be at high risk for dislocation within one year of THA. Direct and indirect costs of dislocation, incremental costs of using DM components, quality-adjusted life-year (QALY) values, and the probabilities of dislocation were derived from published data. The incremental cost-effectiveness ratio (ICER) was established with a willingness-to-pay threshold of $100 000/QALY. Sensitivity analysis was used to examine the impact of variation. Results: In the base case, patients with a spinal deformity were modelled to have an 8% probability of dislocation following primary THA based on published clinical ranges. Sensitivity analysis revealed that, at its current average price ($1000), DM is cost-effective if it reduces the probability of dislocation to 0.9%. The threshold cost at which DM ceased being cost-effective was $1180, while the ICER associated with a DM THA was $71 000 per QALY. Conclusion: These results indicate that under specific clinical and economic thresholds, DM components are a cost-effective form of treatment for patients with spinal deformity who are at high risk of dislocation after THA. Cite this article: Bone Joint J 2018;100-B:1297–1302.